Dialogical approaches to trust in communication - Linell, Per; Marková, Ivana (Advances in cultural psychology., 2014)
Trust has a constituent role in human societies. It has been treated as a scientific topic in many disciplines. Yet, despite the fact that trust and distrust come to life primarily in human communication and through language, it has seldom been analyzed from a communicative or linguistic perspective. This is the theme of this path-breaking volume.This volume contains 12 chapters, plus introduction and epilogue by the editors. They have been authored by leading specialists on trust in language and communication, coming from many disciplines and from different cultures and countries. Most of the authors share a conceptual basis in dialogical theories.This book is a follow-up volume to two previous volumes on trust within cultural psychology, Trust and Distrust (Markov ̀& Gillespie, 2008) and Trust and Conflict (Markov ̀& Gillespie, 2012). It will be of interest to anyone seriously interested in trust in societies, and in trust and distrust as displayed in communication and language.